But Where's the Contract? A Tribute to Professor David McLauchlan - Keene, Amelia; Leslie, Sarah (Victoria University of Wellington Law Review, 2011)
This article is a tribute to Professor David McLauchlan on the occasion of his 40th teaching anniversary. The first part is a personal recollection from each of the two authors. The second part is a joint case note. It poses the question: how could a real estate firm who knew the vendor did not intend to appoint the firm as agent nevertheless have a legal right to withhold commission? In the decision of Nightingale v Barfoot Ltd, Venning J confirmed that the firm had such a right. This article challenges the accuracy of that conclusion, suggesting that as there was no evidence to support the formation of an agency agreement, the real estate firm did not have the right to deduct commission. It analyses critically a number of the legal arguments raised in the case and those that should have been raised, including those concerning contract formation, the objective principle, promissory estoppel, and the effect of s 62 of the Real Estate Agents Act 1976 and the Contracts Privity Act 1982. Much responsibility for the outcome of the case must be pinned on counsel for the vendor, who failed to stop and ask himself "But Where’s The Contract"?